Millennial generation's steps: weaving cultural heritage through pambiwara courses at Permadani studio - Sudarsana, Sudarsana; Wijaya, Mahendra; Pujihartati, Sri Hilmi; Marimin, Marimin; Adi, Yustia Atsanatrilova (Universitas Islam Sultan Agung, 2024)
The millennial generation in Surakarta faces the imperative need to preserve and fortify the essence of Javanese culture amidst the pervasive forces of globalization driven by internet technology. The emergence of Permadani Studio is perceived as a means to aid millennials in understanding and cherishing local culture. However, what is the social structure within the studio and how does it contribute to the preservation of Javanese culture?. This study adopted a qualitative approach, utilizing in-depth interviews and Focus Discussion Groups to explore the role of Permadani Studio in maintaining the richness of Javanese culture among the millennial generation in Surakarta. Data analysis employed descriptive qualitative methods and Anthony Giddens' structuration theory framework to comprehend the interplay between social structure and individual action in the context of cultural preservation. Through the lens of Anthony Giddens' social structuralism approach, the Pambiwara courses at Permadani Studio demonstrate how social structures, such as Javanese cultural norms and values, shape the institutional framework for cultural preservation. Millennials and course instructors are active agents in rejuvenating cultural preservation practices tailored to their era, showcasing the intricate interaction between structure and agency in safeguarding cultural heritage. These findings underscore the significance of collaboration between social structure and individual agents in addressing the challenges posed by globalization to preserve local culture.